(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
Online trading system impacts small and medium entreprsises (SMEs) to easily sell food products and make the sales of processed food and beverage product in Indonesia continues to grow, however their awareness to implement food safety standards is still considered as low. This research was aimed to determine the characteristic and Good Manufacturing Practices (GMP) fulfillment of online SMEs with frozen processed beef and chicken products that is included in medium risk registration categories with BPOM MD authorization. Research methods include sample selection of 24 SMEs respondents in DKI Jakarta with snowball sampling method, questionnaire distribution, field observations and data processing using descriptive analysis. Analysis of GMP fulfillment by MSMEs is based on eight requirements refer to Ministry of Industry Regulation Number 75/M-IND/PER/7/2010 concerning GMP guidelines. Results showed that 41.7% the leader had bachelor degree and 54.2% total assets under 5 million rupiah with annual turnover under 50 million rupiah. Most of them had IUMK (62.5%), production room located in household kitchen (54.2%) and selling online through social media (95.8%). 79.2% of respondents slightly understand about GMP and food safety concept. The most uncomplied from eight requirements of GMP was application of lamp protectors in the production room (91.7%).